Effects of oxidation on the structure of collagen fibers of sea cucumber (Apostichopus japonicus) body wall during thermal processing. (March 2021) - Dong, Xiufang; Yang, Xihong; Li, Hongyan; Che, Hongxia; Song, Lin; Chen, Xing; Xie, Wancui; Qi, Hang
Abstract: Thermal treatment during sea cucumber processing might affect the texture of the final product. In the present study, collagen fibers (CFs) extracted from the body wall of sea cucumber Apostichopus japonicus were used to investigate the effects of heating and oxidative conditions on CFs structure. Hydroxyl radicals (OH) were generated in CFs treated at 37 °C and the intensity of the signal was comparable to samples under oxidative conditions at 4 °C. Release of protein and glycosaminoglycan was observed in CFs heat-treated at 37 °C or under oxidative conditions at 4 °C, leading to the conversion of α-helixes into β-sheets, red shift of amide band I, decrease in thermostability, and scattered arrangement of collagen fibrils. The degree of damage in CFs structure is different among groups. In particular, in thermally- and oxidative treated group, macromolecular fragments remarkably degraded over time, 10 kDa proteins were abundantly released, amide bands A and III showed redshift, and maximum denaturation temperature and decomposition temperature were the lowest compared to other groups. The findings discussed herein reveal the structural changes induced by thermal treatment in sea cucumber CFs and provide an explanation of the mechanism from the view of protein oxidation. Highlights: Hydroxyl radicals (.OH) were generated continuously in CFs at 37 °C over time Heating or additive.OH both induced release of protein and GAG in CFs Heating or additive.OH both reduced structural stability of CFs Heating & additive.OH degraded macromolecular fragment and released 10 kDa protein